Interlinking High School Science with Environment: Some Pedagogical Connections - Sharma, Rashmi (SCHOOL SCIENCE, 2016)
Environmental consciousness is a major theme of almost all global and local deliberations and discussions in today’s time. Environmental education is also an integral part of education at all levels of schooling. As per the guidelines of the Honourable Supreme Court of India, environmental education is a compulsory subject in schools. Apart from this, some topics pertaining to environmental education are a part and parcel of every discipline at school level. However, there are still some gaps reflected in the attitude of our students in regard to environmental awareness and sensitivity.